Jesus - His Transforming Effect - Paul Bharathi (Asosiasi Ahli Filsafat Keilahian Indonesia, 2021)
Transformation of an individual and the society at large is the sole objective of Jesus’ message to his disciples, and in turn, his disciples too preached on the same theme to the believers of Jesus. The first part of the presentation highlights interpreting and understanding Jesus basing on the gospels. The gospels help us to understand Jesus in our own situation and give meaning to our life. As a result, transforming oneself is the most important and meaningful message we learn from the gospels for our life. The second part of the presentation shows how he plays a transformative role in his disciples' lives, and it also gives us an invitation to transform ourselves in our present life. But when we analyze the reality, the believers/disciples are not transformed, rather they remain the same, and their life does not correspond to the teachings of Jesus. They are more preoccupied with observing the rituals and rubrics than following the teachings of Christ in their lives. The third part of the presentation suggests three corrective measures to be taken by every disciple of Jesus, enabling us to transform ourselves and thus live a meaningful life.